Optical grating coupler biosensors - Vörös, J; Ramsden, J.J; Csúcs, G; Szendrő, I; De Paul, S.M; Textor, M; Spencer, N.D (Biomaterials, 2002)
By incorporating a grating in a planar optical waveguide one creates a device with which the spectrum of guided lightmodes can be measured. When the surface of the waveguide is exposed to different solutions, the peaks in the spectrum shift due to molecular interactions with the surface. Optical waveguide lightmode spectroscopy (OWLS) is a highly sensitive technique that is capable of real-time monitoring of these interactions. Since this integrated optical method is based on the measurement of the polarizability density (i.e., refractive index) in the vicinity of the waveguide surface, radioactive, fluorescent or other kinds of labeling are not required. In addition, measurement of at least two guided modes enables the absolute mass of adsorbed molecules to be determined. In this article, the technique will be described in some detail, and applications from different areas will be discussed. Selected examples will be presented to demonstrate how monitoring the modification of different metal oxides with polymers and the response of the coated oxides to biofluids help in the design of novel biomaterials; how OWLS is useful for accurate bioaffinity sensing, which is a key issue in the development of new drugs; and how the quantitative study of protein–DNA/RNA and cell–surface interactions can enhance the understanding of processes in molecular and cellular biology.